Cardiac T1 mapping in non-ST-segment elevation myocardial infarction: temporal changes in myocardial fibrosis - Luis Paiva; Luis Paiva; Maria João Ferreira; Maria João Ferreira; Maria João Ferreira; Sónia Afonso; Sónia Afonso; Paulo Donato; Paulo Donato; Lino Gonçalves; Lino Gonçalves (Frontiers in Cardiovascular Medicine)
IntroductionCardiac magnetic resonance (CMR) imaging allows tracking of ongoing fibrosis modifications following myocardial infarction (MI). We evaluated temporal changes in late gadolinium enhancement (LGE) and extracellular volume fraction (ECV) within the MI culprit coronary artery and remote regions of the myocardium during the index ischemic event and follow-up in patients with NSTEMI.MethodsThis prospective, single-center study included 30 patients with type 1 NSTEMI. It involved the evaluation of patients using coronary angiography, invasive coronary physiology, and biomarkers. CMR imaging was used to assess left ventricular (LV) volume, function, and myocardial fibrosis using LGE and ECV. These assessments were performed at baseline and repeated 6-10 months after MI.ResultsAt the 4-year post-MI follow-up, 27 patients survived [age 65 (58,74) years; 77% male], and LV mass, volume, and contractility remained unchanged between the baseline and follow-up measurements. Myocardial fibrosis assessed using LGE showed a decreasing trend at follow-up (9.4 ± 4.4% vs. 6.7 ± 4.4%; p = 0.051), particularly in the MI culprit coronary artery regions (14.2 ± 8.6% vs. 9.5 ± 7.0%; p = 0.015). LGE volume regression was observed in 70% of cases. The ECV measurements did not change between the initial and follow-up CMR assessments. Despite the high prevalence of multivessel coronary artery disease (CAD) (53%), no significant changes in LGE or ECV measurements were observed in the remote myocardium.ConclusionsAfter NSTEMI, LGE decreased in the heart regions supplied by the culprit coronary arteries. However, the ECV measurements remained unchanged. Multivessel CAD was not associated with significant changes in myocardial fibrosis in the remote myocardium.